(untitled) (Al-Academy, 2017)
The design of the Graphic has recently taken a great variety in the curricula and design methods that have led to its applications for career advancement and aesthetic quality. This is due to the communicative role that it plays in the movement of human beings and their aspirations. Among these applications are the designs of magazine covers in different variations. The design of the cover is based on a structural system that requires awareness and skill from the designer, especially since the organizational structure in the design of the envelope is limited in both vocabulary and space, and in the neighborhood Many have the image of sovereignty and sometimes the other head line, and can lead color values ​​are other. In all cases, the result lies in the organization of the structure and relationships shaping, which leads to the basic purpose of the total of that mix visual form, in the current research, researchers try to address this from the following default: Structural systems role in the design of magazine covers? The importance of the possibility of benefiting employees and workers in the design of magazine covers for the cover of the importance of deliberative communication, and also aims to reach: Structural systems are defined in the design of magazine covers.